Industrial solid waste-based anti-seepage material and preparation method thereof
By using industrial solid waste phosphogypsum, calcium carbide slag and other materials to prepare base anti-seepage materials, the problems of industrial solid waste storage and environmental pollution have been solved, and the resource utilization and anti-seepage performance have been improved.
Patent Information
- Application Number
- CN202411940578.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Industrial solid waste such as phosphogypsum and calcium carbide slag have large storage capacity and low utilization rate, resulting in environmental pollution and waste of resources.
The basic anti-seepage materials are prepared by industrial solid waste phosphogypsum, calcium carbide slag, sand and bentonite. Through the stirring and compaction process, the pH value of the material and the particle grading characteristics are controlled to improve the anti-seepage performance.
The resource utilization of industrial solid waste has been realized, the stock and construction costs of solid waste reservoirs have been reduced, the anti-seepage performance has been improved, and the pollution impact on the environment, soil and groundwater has been reduced.
Smart Images

Figure CN119707428A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of industrial solid waste utilization and environmental geotechnical technology, and in particular to an industrial solid waste-based anti-seepage material and a preparation method thereof. Background Art
[0002] According to the guidance on the comprehensive utilization of bulk solid waste, the comprehensive utilization of solid waste is the top priority for my country to implement the sustainable development strategy in depth. The standardized disposal and utilization of industrial solid waste is bound to become a hot spot in my country's environmental protection work. Using industrial solid waste to replace soil materials is conducive to reducing the cost of materials and realizing the recycling of solid waste, which has a very broad prospect.
[0003] my country is a major producer of phosphate fertilizers, with an annual output of more than 80 million tons of byproduct phosphogypsum. Phosphogypsum is an acidic (pH = 1 ~ 4.5) byproduct produced during the production of phosphate fertilizers and phosphoric acid. It is an industrial solid waste. The main treatment methods for phosphogypsum in my country are stockpiling and resource utilization. At present, the stockpile of phosphogypsum has exceeded 800 million tons, and the utilization rate of phosphogypsum is less than 40%. The main component of phosphogypsum is calcium sulfate dihydrate, and it also contains many other chemical substances, such as silicon dioxide, soluble phosphorus and soluble fluorine. Therefore, it is necessary to reduce the phosphorus and fluorine content in the leachate to reduce pollution to the environment and meet environmental protection requirements.
[0004] Calcium carbide slag is an alkaline solid waste with calcium hydroxide as the main component produced in the process of producing acetylene, polyvinyl chloride (PVC), etc. by the calcium carbide process.
[0005] In view of the current large amount of phosphogypsum and carbide slag stockpiles, it is necessary to utilize them as resources. Summary of the invention
[0006] The present invention provides an industrial solid waste-based anti-seepage material and a preparation method thereof, which adopts the following technical scheme:
[0007] In a first aspect, the present invention provides an industrial solid waste-based anti-seepage material, comprising an anti-seepage material and water; the anti-seepage material comprises solid waste phosphogypsum, solid waste carbide slag, sand, and bentonite.
[0008] Preferably, the anti-seepage material comprises the following raw materials in mass fractions: 21% to 48% of solid waste phosphogypsum, 0% to 1% of solid waste carbide slag, 40% to 60% of sand, and 12% to 18% of bentonite;
[0009] The mass of the water is 5-21% of the mass of the anti-seepage material.
[0010] Preferably, the pH of the solid waste phosphogypsum is 1 to 4.5.
[0011] Preferably, the pH value of the solid waste carbide slag is 11-13.
[0012] Preferably, the solid waste phosphogypsum has the following particle grading characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 The solid waste phosphogypsum has a uniformity coefficient Cu≥5 and a curvature coefficient Cc of 1-3;
[0013] The solid waste carbide slag has the following particle grading characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 The solid waste carbide slag has a non-uniformity coefficient Cu≥5 and a curvature coefficient Cc of 1-3;
[0014] The sand has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 is 0.25-0.30 mm, the unevenness coefficient Cu of the sand is ≥5, and the curvature coefficient Cc is 1-3;
[0015] The bentonite has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 The thickness of the bentonite is 0.25-0.30 mm, the uniformity coefficient Cu is ≥5, and the curvature coefficient Cc is 1-3.
[0016] Preferably, the bentonite includes at least one of sodium-based bentonite, calcium-based bentonite, and sodium-calcium-based bentonite.
[0017] In a second aspect, the present invention further provides a method for preparing the industrial solid waste-based anti-seepage material, comprising the following steps:
[0018] Stirring solid waste phosphogypsum and solid waste carbide slag, and adding water during the stirring process to obtain a first mixture, and controlling the mass ratio of solid waste phosphogypsum and solid waste carbide slag to (21-48): (0-1) to adjust the pH value of the first mixture to 6.5-7.5;
[0019] Adding sand and bentonite to the first mixture and stirring to obtain a second mixture;
[0020] The second mixed material is compacted to obtain an industrial solid waste-based anti-seepage material.
[0021] Preferably, in the step of compacting the second mixed material to obtain the industrial solid waste-based anti-seepage material, the compaction degree is ≥ 90%.
[0022] The industrial solid waste-based anti-seepage material and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0023] The industrial solid waste-based anti-seepage material of the present invention is based on the idea of solid waste utilization and material modification, and uses industrial solid wastes such as phosphogypsum and carbide slag with large output and low utilization rate to study anti-seepage materials, which not only reduces the solid waste stockpile, but also reduces costs; the industrial solid waste-based anti-seepage material of the present invention, carbide slag can adjust the phosphogypsum leachate, make the leachate pH tend to be neutral and reduce the content of soluble elements P and F, environmentally friendly and safe, good anti-seepage performance, and minimize the impact on the surrounding environment, soil and groundwater. The environmentally friendly composite anti-seepage material of the present invention, solid waste phosphogypsum and carbide slag do not need any pretreatment, can be used directly, and is convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 The permeability coefficient and leachate pH value diagram of the industrial solid waste-based anti-seepage material of Examples 1 to 2 and 4;
[0026] Figure 2 This is a SEM microscopic image of a soil sample after the permeability test of the industrial solid waste-based anti-seepage material prepared in Example 1 was completed. At this time, the soil sample has more pores;
[0027] Figure 3 This is a SEM microscopic image of the soil sample after the permeability test of the industrial solid waste-based anti-seepage material prepared in Example 2 was completed. At this time, the soil sample is dense and has tiny pores;
[0028] Figure 4 This is a SEM microscopic image of the soil sample after the permeability test of the industrial solid waste-based anti-seepage material prepared in Example 3 was completed. At this time, the soil sample has more pores. DETAILED DESCRIPTION
[0029] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.
[0032] An embodiment of the present application provides an industrial solid waste-based anti-seepage material, including an anti-seepage material and water; the anti-seepage material includes solid waste phosphogypsum, solid waste carbide slag, sand, and bentonite.
[0033] The industrial solid waste-based anti-seepage material of the present invention comprises solid waste phosphogypsum and solid waste carbide slag. The industrial solid waste phosphogypsum and carbide slag are used to realize resource utilization of phosphogypsum and carbide slag, save land resources, and reduce construction costs. The direct use of phosphogypsum will lead to acidity of the leachate and high content of soluble elements P and F, so carbide slag is added for adjustment. Under alkaline conditions, Ca in the carbide slag is reduced. 2+ Reacts with water-soluble phosphorus in phosphogypsum to form phosphate lime Ca3(PO4) 2 , Ca 2+ It reacts with the water-soluble fluorine in phosphogypsum to generate CaF2, realizing the resource utilization of solid waste, saving land resources, and reducing construction costs.
[0034] In some embodiments, the anti-seepage material includes the following raw materials in mass fractions: solid waste phosphogypsum 21% to 48%, solid waste carbide slag 0% to 1%, sand 40% to 60%, and bentonite 12% to 18%;
[0035] The mass of water is 5 to 21% of the mass of the anti-seepage material.
[0036] In some embodiments, the pH of the solid waste phosphogypsum is 1 to 4.5, which is highly acidic.
[0037] In some embodiments, the pH value of solid waste carbide slag is 11-13, which is relatively alkaline. Solid waste carbide slag accounts for 0%-1% of the total weight of the material, and the proportion of solid waste carbide slag includes but is not limited to this range, which can adjust the pH value of the anti-seepage composite material leachate to 6-8.
[0038] In some embodiments, the solid waste phosphogypsum has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 It is 0.25~0.30mm, the uniformity coefficient Cu of solid waste phosphogypsum is ≥5, and the curvature coefficient Cc is 1~3.
[0039] In some embodiments, the solid waste carbide slag has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 It is 0.25~0.30mm, the uniformity coefficient Cu of solid waste carbide slag is ≥5, and the curvature coefficient Cc is 1~3.
[0040] In some embodiments, the sand has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 It is 0.25~0.30mm, the uniformity coefficient of sand Cu≥5, and the curvature coefficient Cc is 1~3.
[0041] In some embodiments, the bentonite has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 It is 0.25~0.30mm, the uniformity coefficient of bentonite Cu≥5, and the curvature coefficient Cc is 1~3.
[0042] The particle sizes of solid waste phosphogypsum, solid waste carbide slag, sand and bentonite include but are not limited to this range, which can make the gradation of the anti-seepage composite material good, the uniformity coefficient Cu>5, and the curvature coefficient Cc between 1 and 3.
[0043] In some embodiments, bentonite includes at least one of sodium-based bentonite, calcium-based bentonite, and sodium-calcium-based bentonite; bentonite accounts for 12 to 18% of the total weight of the material. Bentonite mineral resources are abundant, widely distributed, and complete in variety, among which calcium-based bentonite is the most common. In the research and development of anti-seepage materials, by increasing the use of bentonite, the large pores in phosphogypsum, carbide slag and sand mixtures can be effectively filled. When water penetrates into bentonite, its volume expands, thereby preventing water flow, which significantly improves the anti-seepage performance of anti-seepage materials.
[0044] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned industrial solid waste-based anti-seepage material, comprising the following steps:
[0045] S1, stirring solid waste phosphogypsum and solid waste carbide slag, and adding water during the stirring process to obtain a first mixture, and controlling the mass ratio of solid waste phosphogypsum and solid waste carbide slag to (21-48): (0-1) to make the pH value of the first mixture 6.5-7.5;
[0046] S2, adding sand and bentonite to the first mixture, stirring, to obtain a second mixture;
[0047] S3. Compact the second mixture to obtain an industrial solid waste-based anti-seepage material.
[0048] In some embodiments, in the step of compacting the second mixed material to obtain an industrial solid waste-based anti-seepage material, the compaction degree is ≥ 90%.
[0049] Specifically, compaction degree, also known as tamping degree, refers to the ratio of the dry density of soil or other road construction materials after compaction to the standard maximum dry density, expressed as a percentage.
[0050] The industrial solid waste-based anti-seepage material of the present invention is based on the idea of solid waste utilization and material modification, and uses industrial solid wastes such as phosphogypsum and carbide slag with large output and low utilization rate to study anti-seepage materials, which not only reduces the solid waste stockpile, but also reduces costs; the industrial solid waste-based anti-seepage material of the present invention, carbide slag can adjust the phosphogypsum leachate, make the leachate pH tend to be neutral and reduce the content of soluble elements P and F, environmentally friendly and safe, good anti-seepage performance, and minimize the impact on the surrounding environment, soil and groundwater. The environmentally friendly composite anti-seepage material of the present invention does not require any treatment of solid waste phosphogypsum and carbide slag, and can be used directly, which is convenient.
[0051] The industrial solid waste-based anti-seepage material and its preparation method of the present application are further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0052] In the following examples, the pH of phosphogypsum is 2.96, and the moisture content (mass moisture content) excluding bound water is 10.6%; the pH of carbide slag is 12.95, the moisture content (mass moisture content) is 0.58%, and the CaO content (mass content) is 67.87%; the bentonite is calcium-based bentonite purchased from Shijiazhuang Tourmaline Mineral Products Co., Ltd., item number lsxky0045.
[0053] Example 1
[0054] The embodiment of the present application provides an industrial solid waste-based anti-seepage material, including an anti-seepage material and water; the anti-seepage material includes the following raw materials in mass fractions: 48% of solid waste phosphogypsum, 0% of solid waste carbide slag, 40% of sand, and 12% of bentonite; the mass of water is 15% of the mass of the anti-seepage material;
[0055] Solid waste phosphogypsum has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste phosphogypsum Cu=19.2, and the curvature coefficient Cc is 1.16;
[0056] Solid waste carbide slag has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste carbide slag Cu=19.2, and the curvature coefficient Cc is 1.16;
[0057] Sand has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the sand unevenness coefficient Cu=19.2, and the curvature coefficient Cc is 1.16;
[0058] Bentonite has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 It is 0.28mm, the uniformity coefficient of bentonite Cu=19.2, and the curvature coefficient Cc is 1.16.
[0059] The method for preparing the above-mentioned industrial solid waste-based anti-seepage material comprises the following steps:
[0060] S1, placing solid waste phosphogypsum and solid waste carbide slag in a stirrer for stirring and mixing, continuously adding water during stirring, stirring evenly, to obtain a first mixture;
[0061] S2, adding sand and bentonite to the first mixture, and continuing to stir to obtain a second mixture;
[0062] S3. Compact the second mixed material to a compaction degree of 90% to obtain an industrial solid waste-based anti-seepage material.
[0063] Example 2
[0064] The embodiment of the present application provides an industrial solid waste-based anti-seepage material, including an anti-seepage material and water; the anti-seepage material includes the following raw materials in mass fractions: 47.5% of solid waste phosphogypsum, 0.5% of solid waste carbide slag, 40% of sand, and 12% of bentonite; the mass of water is 21% of the mass of the anti-seepage material;
[0065] Solid waste phosphogypsum has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste phosphogypsum Cu=19.2, and the curvature coefficient Cc is 1.16;
[0066] Solid waste carbide slag has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste carbide slag Cu=19.2, and the curvature coefficient Cc is 1.16;
[0067] Sand has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the sand unevenness coefficient Cu=19.2, and the curvature coefficient Cc is 1.16;
[0068] Bentonite has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 It is 0.28mm, the uniformity coefficient of bentonite Cu=19.2, and the curvature coefficient Cc is 1.16.
[0069] The method for preparing the above-mentioned industrial solid waste-based anti-seepage material comprises the following steps:
[0070] S1, placing solid waste phosphogypsum and solid waste carbide slag in a stirrer for stirring and mixing, continuously adding water during stirring, stirring evenly, to obtain a first mixture;
[0071] S2, adding sand and bentonite to the first mixture, and continuing to stir to obtain a second mixture;
[0072] S3. Compact the second mixed material to a compaction degree of 90% to obtain an industrial solid waste-based anti-seepage material.
[0073] Example 3
[0074] The embodiment of the present application provides an industrial solid waste-based anti-seepage material, including an anti-seepage material and water; the anti-seepage material includes the following raw materials in mass fractions: 47% of solid waste phosphogypsum, 1% of solid waste carbide slag, 40% of sand, and 12% of bentonite; the mass of water is 15% of the mass of the anti-seepage material;
[0075] Solid waste phosphogypsum has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste phosphogypsum Cu=19.2, and the curvature coefficient Cc is 1.16;
[0076] Solid waste carbide slag has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste carbide slag Cu=19.2, and the curvature coefficient Cc is 1.16;
[0077] Sand has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the sand unevenness coefficient Cu=19.2, and the curvature coefficient Cc is 1.16;
[0078] Bentonite has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 It is 0.28mm, the uniformity coefficient of bentonite Cu=19.2, and the curvature coefficient Cc is 1.16.
[0079] The method for preparing the above-mentioned industrial solid waste-based anti-seepage material comprises the following steps:
[0080] S1, placing solid waste phosphogypsum and solid waste carbide slag in a stirrer for stirring and mixing, continuously adding water during stirring, stirring evenly, to obtain a first mixture;
[0081] S2, adding sand and bentonite to the first mixture, and continuing to stir to obtain a second mixture;
[0082] S3. Compact the second mixed material to a compaction degree of 90% to obtain an industrial solid waste-based anti-seepage material.
[0083] Example 4
[0084] The embodiment of the present application provides an industrial solid waste-based anti-seepage material, including an anti-seepage material and water; the anti-seepage material includes the following raw materials in mass fractions: 46.5% of solid waste phosphogypsum, 1.5% of solid waste carbide slag, 40% of sand, and 12% of bentonite; the mass of water is 15% of the mass of the anti-seepage material;
[0085] Solid waste phosphogypsum has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste phosphogypsum Cu=19.2, and the curvature coefficient Cc is 1.16;
[0086] Solid waste carbide slag has the following particle grading characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the non-uniformity coefficient of solid waste carbide slag Cu=19.2, and the curvature coefficient Cc is 1.16;
[0087] Sand has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 is 0.28mm, the sand unevenness coefficient Cu=19.2, and the curvature coefficient Cc is 1.16;
[0088] Bentonite has the following particle size distribution characteristics: d 10 0.019mm, d 30 0.076mm, d 60 It is 0.28mm, the uniformity coefficient of bentonite Cu=19.2, and the curvature coefficient Cc is 1.16.
[0089] The method for preparing the above-mentioned industrial solid waste-based anti-seepage material comprises the following steps:
[0090] S1, placing solid waste phosphogypsum and solid waste carbide slag in a stirrer for stirring and mixing, continuously adding water during stirring, stirring evenly, to obtain a first mixture;
[0091] S2, adding sand and bentonite to the first mixture, and continuing to stir to obtain a second mixture;
[0092] S3. Compact the second mixed material to a compaction degree of 90% to obtain an industrial solid waste-based anti-seepage material.
[0093] Comparative Example 1
[0094] Comparative Example 1 discloses a phosphogypsum composite sand anti-seepage material with self-healing properties of cracks and a preparation method thereof, specifically the preparation of sample No. 3 in the embodiment of the specification in patent CN115925380A - Phosphogypsum composite sand anti-seepage material with self-healing properties of cracks and a preparation method thereof.
[0095] Performance Testing
[0096] The mass fractions of raw materials and permeability coefficients of the industrial solid waste-based anti-seepage materials in Examples 1 to 4 and the anti-seepage materials in Comparative Example 1 are shown in Table 1. The permeability coefficients of the environmentally friendly anti-seepage composite industrial solid waste-based anti-seepage materials in Examples 1 to 4 are saturated permeability coefficients measured by a consolidation permeameter, and the test is based on the constant head permeability test in GB / T 50123-2019; the permeability coefficient of the anti-seepage material in Comparative Example 1 is measured by a variable head permeability test.
[0097] Table 1 - Mass fraction and permeability coefficient of each raw material in different embodiments
[0098]
[0099] The industrial solid waste-based anti-seepage materials prepared in Examples 1, 2 and 4 were subjected to permeation tests and the pH value and P and F contents of the leachate were measured. The results are shown in Table 2. The P and F contents of the leachate were determined by ion chromatography, and the instrument used was the American Thermo Fisher Scientific AQUION RFIC.
[0100] Table 2 - pH value and P, F content measurement results of industrial solid waste based anti-seepage materials leachate in different embodiments
[0101] Example Phosphogypsum (%) Carbide slag (%) pH P concentration of leachate (mg / L) F concentration of leachate (mg / L) Example 1 48 0 3.6 618.15 234.27 Example 2 47.5 0.5 7.3 0.1 14.83 Example 4 46.5 1.5 11.7 0.085 14.55
[0102] It can be seen from the permeability coefficient results of Examples 1 to 4 in Table 1 that the permeability coefficient can be reduced by about 1 order of magnitude when 0.5% carbide slag is added compared to no carbide slag, and the permeability coefficient when 0.5% to 1% carbide slag is added is lower than when no carbide slag is added. Combined with the pH value and P and F content measurement results of the leachate in Table 2, it can be seen that after adding 0.5% carbide slag, the ratio of carbide slag to phosphogypsum is about 1:95, and the pH value tends to be neutral, which is conducive to the expansion of bentonite, so that the mixture of bentonite, phosphogypsum and carbide slag can be better filled in the gaps between sand particles, thereby reducing the permeability coefficient; and the P and F percolation concentrations are greatly reduced, both below the limit values of the "Hazardous Waste Leaching Discrimination Standard" (GB5085.3-2007). However, when the carbide slag dosage is 1.5%, the pH of the leachate is alkaline, which is not conducive to the expansion of bentonite, thereby increasing the permeability coefficient.
[0103] Figure 1 These are the permeability coefficients and leachate pH values of the industrial solid waste-based anti-seepage materials of Examples 1 to 2 and 4.
[0104] Figure 1 The relationship between the permeability coefficient and pH value of the anti-seepage materials prepared in different embodiments can be intuitively reflected.
[0105] In Table 1, the permeability coefficient of Example 2 is lower than that of Comparative Example 1, but the phosphogypsum used in Comparative Example 1 is washed phosphogypsum, and the bentonite is modified by polyacrylamide polymer, which greatly increases the cost and complexity of material preparation. In comparison, Example 2 has the advantages of convenient process and lower cost.
[0106] Figure 2 This is a SEM microscopic image of the soil sample after the permeability test of the industrial solid waste-based anti-seepage material prepared in Example 1 was completed. Figure 2 It can be seen that the montmorillonite in the bentonite is attached to and wrapped on the surface of the sand particles and phosphogypsum particles. However, the acidic environment brought by the phosphogypsum inhibits the expansion of the bentonite, so that only part of the pores between the sand particles and the plate-like phosphogypsum are filled, and there are many pores.
[0107] Figure 3 This is a SEM microscopic image of the soil sample after the permeability test of the industrial solid waste-based anti-seepage material prepared in Example 2 was completed. Figure 3 It can be seen that due to the addition of 0.5% carbide slag, the main component Ca(OH)2 in the carbide slag reacts with the free acid in the phosphogypsum to make the sample neutral, thereby effectively improving the expansion properties of the bentonite. In the electron microscope scanning image, it can be seen that the pores between the sand particles are filled with bentonite. At this time, the sample mixture presents a relatively dense microstructure, which has a good barrier effect on the seepage of water.
[0108] Figure 4This is a SEM microscopic image of the soil sample after the permeability test of the industrial solid waste-based anti-seepage material prepared in Example 3 was completed. Figure 4 It can be seen that when 1.5% carbide slag is added, the free acid in the phosphogypsum is completely neutralized, and the excess carbide slag makes the sample alkaline, which inhibits the expansion properties of bentonite and results in more pores between the sand particles and the plate-like phosphogypsum.
[0109] The anti-seepage material of the present invention has a significant anti-seepage effect, and the solid waste carbide slag is added to the solid waste phosphogypsum to greatly reduce the impact on the surrounding environment. The anti-seepage material uses industrial solid wastes such as phosphogypsum and carbide slag with large output and low utilization rate to conduct anti-seepage material research, realizes the resource utilization of solid waste, saves land resources, and reduces construction costs.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An industrial solid waste-based anti-seepage material, characterized in that: It includes anti-seepage materials and water; the anti-seepage materials include solid waste phosphogypsum, solid waste carbide slag, sand and bentonite.
2. The industrial solid waste-based anti-seepage material according to claim 1, characterized in that: The anti-seepage material comprises the following raw materials in mass fractions: 21% to 48% of solid waste phosphogypsum, 0% to 1% of solid waste carbide slag, 40% to 60% of sand, and 12% to 18% of bentonite; The mass of the water is 5-21% of the mass of the anti-seepage material.
3. The industrial solid waste-based anti-seepage material according to claim 1, characterized in that: The pH value of the solid waste phosphogypsum is 1 to 4.
5.
4. The industrial solid waste-based anti-seepage material according to claim 1, characterized in that: The pH value of the solid waste carbide slag is 11-13.
5. The industrial solid waste-based anti-seepage material according to claim 1, characterized in that: The solid waste phosphogypsum has the following particle grading characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 The solid waste phosphogypsum has a uniformity coefficient Cu≥5 and a curvature coefficient Cc of 1-3; The solid waste carbide slag has the following particle grading characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 The solid waste carbide slag has a non-uniformity coefficient Cu≥5 and a curvature coefficient Cc of 1-3; The sand has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 is 0.25-0.30 mm, the unevenness coefficient Cu of the sand is ≥5, and the curvature coefficient Cc is 1-3; The bentonite has the following particle size distribution characteristics: 10 0.015~0.025mm, d 30 0.07~0.08mm, d 60 The thickness of the bentonite is 0.25-0.30 mm, the uniformity coefficient Cu is ≥5, and the curvature coefficient Cc is 1-3.
6. The industrial solid waste-based anti-seepage material according to claim 1, characterized in that: The bentonite includes at least one of sodium-based bentonite, calcium-based bentonite, and sodium-calcium-based bentonite.
7. A method for preparing an industrial solid waste-based anti-seepage material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Stirring solid waste phosphogypsum and solid waste carbide slag, and adding water during the stirring process to obtain a first mixture, and controlling the mass ratio of solid waste phosphogypsum and solid waste carbide slag to (21-48): (0-1) to adjust the pH value of the first mixture to 6.5-7.5; Adding sand and bentonite to the first mixture and stirring to obtain a second mixture; The second mixed material is compacted to obtain an industrial solid waste-based anti-seepage material.
8. The method for preparing the industrial solid waste-based anti-seepage material according to claim 7, characterized in that: In the step of compacting the second mixed material to obtain an industrial solid waste-based anti-seepage material, the degree of compaction is ≥ 90%.
Citation Information
Patent Citations
Phosphogypsum ball and preparation method and application thereof
CN103482896A
Novel environment-friendly phosphogypsum-based impermeable material
CN108751890A
Phosphogypsum-based mine filling cementing material
CN115504753A